Phytochemicals, Heavy Metals, and Antioxidant Vitamins Assessment in Tomatoes (Solanum lycopersicum) Cultivated Near Cement Company Firm of Sokoto, Nigeria - Kabiru Sirajo; Zulkallaini Shehu; Anas Bello; Ibrahim Mas’ud; Kabiru Muhammad Nata’ala (Food ScienTech Journal, 2023)
Even at low concentrations, it is well known that vegetables can readily absorb metals from contaminated soil or deposits on air-exposed plant parts. These metals then build up at high levels in the edible parts of the vegetables. Vegetables are a significant part of the human diet; hence heavy metal poisoning of these food items cannot be understated.  As a result, this study sought to quantify the amounts of phytochemicals, heavy metals, and antioxidant vitamins in tomatoes grown close to the Cement Company of Northern Nigeria (Sokoto Cement). Phytochemicals, heavy metals, and antioxidant vitamins were determined using standard analytical procedures. The study confirmed the presence of flavonoids, saponins, alkaloids tannins, steroids, and volatile oils. The heavy metals detected (Cu, Zn, Cd and Cr) were found below the WHO safe limits guidelines apart from Cr which exceed WHO safe limit guidelines. Substantial amounts of vitamin A, C and E were also observed. It was concluded that tomatoes cultivated in Kalambaina area are safe for consumption in terms of heavy metals.